EMPLOYEE’S RIGHT TO PRIVACY AS AN ESSENTIAL PART OF DECENT WORK - Jovanović, Predrag P; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Inter alia, personal integrity is protected with right to privacy. In that context we can observe employee’s right to privacy as an integral part of occupational safety and health. Personal integrity protection provide adequate health and working ability which is indispensable for productive work. Productive work is vital for employment relationship and represents compatibility of employer’ and employee’ intrests in employment relationship. But in employment relation employer has supervisory prerogatives to provide profit. Employer’s supervisory prerogatives may lead to violation of employee’s right to privacy at work. About that, essential questions are – on which conditions and on which proportion employer may restrict employee’s right to privacy at work? Authors of this paper tried to answer to these questions relying on legal standards in international  law.